Basicranial osteology of Colbertia lumbrerense Bond, 1981 (Mammalia: Notoungulata) - Garcia Lopez, Daniel Alfredo (2011)
A description of Colbertia lumbrerense Bond (Mammalia, Notoungulata) is presented. This species is recorded in levels of the Lumbrera Formation (Eocene) in northwestern Argentina. Several specimens were collected; yet its cranial osteology has not been studied in detail. The new description provided herein is based on five specimens, including the type specimen. The external surface of the posterior zone of the skull in this species shows a generalized notoungulate morphology. The development of certain elements (external auditory meatus, meatal crest, epitympanic sinus) is similar to that observed in other Paleogene notoungulates such as Simpsonotus Pascual, Vucetich, and Fernández; Brachystephanus Simpson, Minoprio, and Patterson; and Xenostephanus Simpson, Minoprio, and Patterson. In spite of this generalized arrangement, the skull shows some distinctive features, particularly in the petrosal. Some traits of this bone are shared with Dolichostylodon saltensis García López and Powell, a notoungulate recorded in upper levels of the same formation. The morphology described in this study is consistent with recent phylogenetic analyses of Paleogene notoungulate taxa that place C. lumbrerense in a basal position.